Superplastic aluminium-lithium matrix composites - Tan, Ming Jen (2008)
The investigations in this project involved the development of a powder metallurgy (P/M) route for the processing of metal-matrix composites, consisting of powder mixing, degassing, cold isostatic pressing (CIP) and hot extrusion, for the production of 0.8um Silicon Carbide particulate (SiCp) reinforced aluminium-lithium 8090 alloy composite.